Application of Importance Performance Analysis (Ipa) Method to Develop Intellectual Capital in Creative SMEs - Sudarijati, Sudarijati; Arsyad, Apendi; Harini, Sri (JURNAL AGRIBISAINS, 2023)
Creative SMEs in Bogor face increasingly sharp competition, both from domestic and foreign products. To support creative SMEs in producing quality products, the role of intellectual capital is very important. Intellectual capital plays a role in improving employee performance and in the long term will influence the performance of SMEs. Apart from that, this capital can be used as a tool to evaluate employee performance so that companies can anticipate the needs of SMEs in the future. This research aims to determine the extent to which the quality of intellectual capital meets the satisfaction and expectations of Creative SME managers as well as strategies for developing the quality of intellectual capital. Data collection was carried out through observations, distributing questionnaires and interviews. Data analysis uses the IPA (Importance Performance Index) method. The sampling technique used purposive sampling, with the number of respondents being 100 Creative UKM managers. The results of the IPA analysis of 43 attributes show that the information system in providing accurate and up-to-date data as well as production SOPs must be evaluated and improved. Apart from that, the speed of the transaction processing performance also needs to be improved. Based on the gap analysis between actual performance and expectations, it shows that the level of conformity between performance and expectations in intellectual capital is in the very suitable category. The intellectual capital development strategy includes conducting training on e-commerce for creative SME entrepreneurs and preparing SOPs related to SME operational functions.